PCR and qPCR for detection of Porcine Circovirus type 2 (PCV2) in captive collared (Pecari tajacu) and white-lipped (Tayassu pecari) peccaries from Southern Brazil - Ullmann, Leila Sabrina [UNESP]; Gravinatti, Mara Lucia; Yamatogi, Ricardo Seiti [UNESP]; Dos Santos, Leonilda Correia; Da Cruz, Taís Fukuta [UNESP]; De Moraes, Wanderlei; Cubas, Zalmir Silvino; De Barros Filho, Ivan Roque; Vidotto, Odilon; Araújo, João Pessoa [UNESP]; Da Costa Vieira, Rafael Felipe; Biondo, Alexander Welker (Universidade Estadual de Londrina, 2016)
Porcine circovirus type 2 (PCV2) is an emergent virus found in commercial pig farms and may cause clinical or subclinical infection. The collared peccary (Pecari tajacu) and white-lipped peccary (Tayassu pecari) may also be infected by PCV2. Accordingly, the aim of this study was to identify PCV2 in whole blood samples of captive peccaries (16 collared and 6 white-lipped) by conventional and quantitative PCR (qPCR). Although the housekeeping gene (c-myc) DNA was successfully amplified, all 22 peccaries tested were negative for PCV2 by both molecular methods. In conclusion, although PCV2 may be endemic in free ranging wild pigs of Central and Northern Brazil, lack of serological and molecular PCV2 evidence (in whole blood) of both captive and free-range wild pigs may indicate low risk of disease in Southern Brazil.
Keywords: PCV2; Peccary; Wildlife swine